A Hero’s Journey: A study on The Dark Knight Trilogy - Reji, Sheedhal K; K, Sreena (International Journal of Psychosocial Rehabilitation, 2020)
The media franchise of Batman (comics, films, novels, television, cartoons and television) stands out from any other forms of written or visual texts with its diversity in artists, audience and expression forms. Perception of the various artists, understanding the audience and Batman’s effect on them helps understand the changing American trends and culture. This research attempts to comprehend the delineation of the journey of a hero of western concept of The Dark Knight Trilogy directed by Christopher Nolen. Joseph Campbell’s ‘Hero’s Journey’ helps in measuring the insights of a hero, where the character undergoes a remarkable cycle of transformation. The study employs the method of qualitative content analysis to understand the complexities and burdens that obscure the hero, his journey of transformation, self-realization and understanding the world they form a part of.